Determination of Reduced Nicotinamide Adenine Dinucleotide with a Protamine Multiwalled Carbon Nanotube Electrode. (22nd January 2016) - Chen, Yan; Yin, Lingling; Li, YiWei; Ma, Yaohong; Yang, Junhui; Meng, Qingjun; Shi, Jianguo
ABSTRACT: A bionanocomposite prepared from multiwalled carbon nanotubes and protamine sulfate is reported for the electrocatalytic determination of dihydronicotinamide adenine dinucleotide. Protamine sulfate was adsorbed via π-π interactions and hydrogen bonds between protonated amines on arginine and surface groups on the multiwalled carbon nanotubes. The multiwalled carbon nanotube protamine composite accumulated dihydronicotinamide adenine dinucleotide on the electrode surface, resulting in high sensitivity and a low limit of detection for dihydronicotinamide adenine dinucleotide. The nanocomposite was employed for dehydrogenase-based biosensing. Alcohol dehydrogenase was allowed to adsorb on the bionanocomposite surface and the sensitivity of the resulting electrode to ethanol was measured. The alcohol biosensor had an excellent sensitivity of 738.5 µA/mM with a low limit of detection of 50 nM.